MEMAHAMI GAYA DAN TIPE KEPEMIMPINAN - Hidayat, Alfi Syahrina; Lestari, Putri; Hasibuan, Nadhilah; Nazuha, Salsabila; Suprianto, Yasmin Novithaharah; Wasiyem, Wasiyem (Politeknik Bisnis Indonesia, 2024)
In this case, influencing the behavior of others, the style and type of leader are closely related to the norms they have. Theoretical research that discusses the types and styles of leadership is needed because these concepts have many variations. This study reviews the literature from a number of primary sources. According to research, there are several different forms of leadership, including authoritarian (autocratic), paternalistic, charismatic, democratic, and military. On the other hand, leadership includes the following: democratic, delegative, bureaucratic, laissez-faire, authoritarian, charismatic, diplomatic, moralistic, administrative, analytical, entrepreneurial, visionary, situational, and militaristic.